Nuclear Changes in the Form of Karyorrhexis and Karyopyknosis in Oral Mucosal Epithelial Cells of Smokers - Adlina Putri Harissa (Indonesian Dental Association, 2025)
Smoking not only has systemic effects but also lead to the development of pathological conditions in the oral cavity. Long-term smoking habits and the carcinogenic substances in cigarettes can decrease the development of epithelial cells and enhance cell apoptosis. Cell death or apoptosis can be characterized by changes in the cell nucleus in form of karyorrhexis and karyopyknosis. Method: This analytical observational research using exfoliative cytology examination with scraping technique was done to evaluate the number and percentage of karyorrhexis and karyopyknosis of oral mucosal epithelial cells. As much as 60 research subjects were used in this study which divided into 30 smokers and 30 non-smokers. Two slides were created from each oral buccal mucous epithelium cell smears that delivered to the laboratory for Papanicolaou staining. Cells observation was conducted in three fields of each slide to evaluate the percentage of cells experiencing karyorrhexis and karyopyknosis. Results: karyorrhexis and karyopyknosis was found higher in smoking subjects. There was significant difference in the number of oral mucosal epithelial cells that undergo kariopyknosis (p=0.005<0.05) and karyorrhexis (p=0.001 <0.05) between smokers and non-smokers group. Conclusion: Smoking can be a causing factor for the cell death in form of an increase of karyopyknosis and karyorrhexis of cells.